Orcovita varungan n. sp. (Crustacea: Decapoda: Varunidae) from Muna Island, southern Sulawesi, Indonesia - Ng, Peter K. L.; Naruse, Tohru (Zootaxa, 2024)
A new species of anchialine crab, Orcovita varungan n. sp., is described from Muna Island in southeastern Sulawesi, Indonesia. This is the second species of this genus known from Indonesia. The new species belongs to the same group of species as O. gracilipes P.K.L. Ng, Guinot & Iliffe, 1996 (from Niue) and O. mcneiceae N.K. Ng & P.K.L. Ng, 2002 (from Loyalty Islands, New Caledonia), with its members possessing a single epibranchial tooth, a prominent tuft of setae between the cheliped fingers of at least male, relatively longer and more slender ambulatory legs, and lacking obviously raised post-frontal lobes. Orcovita varungan n. sp., however, can easily be distinguished from O. gracilipes and O. mcneiceae by its relatively narrower carapace, proportionally longer ambulatory legs and structure of the male first gonopod.